Hypoglycemic Effect of Combination of Azadirachta indica A. Juss. and Gynura procumbens (Lour.) Merr. Ethanolic Extracts Standardized by Rutin and Quercetin in Alloxan-induced Hyperglycemic Rats - Anggit Listyacahyani Sunarwidhi; Sudarsono Sudarsono; Agung Endro Nugroho (Tabriz University of Medical Sciences, 2014)
Purpose: Exploration of plant combinations could be an alternative approach for diabetes treatment. The aim of this study is to evaluate the hypoglycemic effect of combination of A. indica and G. procumbens ethanolic extract s in alloxan - induce d diabetic rats. Metho ds : Powder of A. indica and G. procumbens leaves were macerated with ethanol 70%. Determination of rutin in A. indica and quercetin in G. procumbens w ere performed by TLC - densitometry. Hyperglycemia in rats was induced by an intraperitoneal injection of alloxan monohydrate at a single dose of 150 mg/kgBW. The rats were treated with 3 dosage variation of combinations for 15 days. Hypoglycemic effect was evaluated by estimating the blood glucose levels and the rats pancreas histological study . Results: A. i ndica contained 2. 90 ±0.15% of rutin and G. procumbens contained 18.86±0.86% of quercetin. Combination at the ratio of 50mg/kgBW A. indica : 112.5mg/kgBW G. procumbens showed the highest hypoglycemic effect: 68 . 74±4 . 83% (preprandial) and 73 . 9 1 ±3 . 18% (postprandial). Histolog ical studies indicated that this combination improved the mor ph ology of the islets of Langerhans and β cells. It also increased insulin expression and decreased the elevated - glucose concentrations . Conclusion: This study showed that combination of both extracts has better hypoglycemic effect than the single treatment of A. indica or G. procumbens . Combination of both extracts was potential to develo p as a blood glucose - lowering agent for diabetic patients.